2010
DOI: 10.1007/s10800-010-0226-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical reforming of an acidic aqueous glycerol solution on Pt electrodes

Abstract: The feasibility of the electrochemical conversion of glycerol to alternative, more valuable compounds was evaluated with platinum electrode under galvanostatic conditions. The results indicated a potentially good feasibility of reforming glycerol by electrolysis, particularly under strong acidic conditions (pH 1). Indeed, under controlled conditions at pH 1, various commercially valuable compounds, such as propanediol, glycidol, and 2-propenol, amongst others, were produced. The mechanism for the generation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…In this context, the process Downloaded by [Princeton University] at 04: 47 17 September 2013 intensification technology provides many choices. As demonstrated in recent studies, in situ adsorption, supercritical fluids, membrane catalysts or reactors, microchannel reactors, reactive distillation, microwave heating, photoor electric-catalysts were able to intensify some catalytic reactions for the conversion of glycerol (402,403). However, many other process intensification methods remain untouched in the catalytic conversion of glycerol.…”
Section: Summary and Future Prospectsmentioning
confidence: 96%
“…In this context, the process Downloaded by [Princeton University] at 04: 47 17 September 2013 intensification technology provides many choices. As demonstrated in recent studies, in situ adsorption, supercritical fluids, membrane catalysts or reactors, microchannel reactors, reactive distillation, microwave heating, photoor electric-catalysts were able to intensify some catalytic reactions for the conversion of glycerol (402,403). However, many other process intensification methods remain untouched in the catalytic conversion of glycerol.…”
Section: Summary and Future Prospectsmentioning
confidence: 96%
“…The first aspect is related to water adsorption and activation reaction. For the second aspect, Kongjao et al have detected numerous C1–C6 reaction products with different oxidation levels during the electrochemical reforming of glycerol on Pt electrodes . The number of hydrogen molecules formed is lower than the theoretical one for the complete oxidation of glycerol into CO 2 : normalC normalH 2 normalO normalH CHOH normalC normalH 2 normalO normalH 0.25em prefix+ 0.25em 3 0.25em H 2 normalO 3 0.25em normalC normalO 2 + 0.25em 7 0.25em H 2 . …”
Section: Electrolysis Of Alcohol For Clean Hydrogen Productionmentioning
confidence: 98%
“…Catalytic steam reforming Advantages • Lower reaction temperatures (<100 • C) making possible a rapid startup • Low toxicity • Direct pure hydrogen production, separated from other reaction products • Easier and fast control of hydrogen production rate • Compact unit combining both reaction and hydrogen purification with a consequent capital costs reduction • High renewable energy integration • Reduced environmental impact • Seasonal energy storage without energy losses • Capability to handle power fluctuations by H2 production • Lower power demands than water electrolysis, since part of the energy required is provided by the organic molecule this context, recent studies have shown that the electrochemical reforming of water-alcohol mixtures, i.e., methanol [5][6][7][8], glycerol [9,10], ethanol [11,12], bioethanol [13,14] and ethylene glycol [15] has a great potential for H 2 production at atmospheric pressure. The use of such compounds allows electrolysis at potentials lower than 1.2 V, leading to electrical power savings if compared to conventional electrolytic water splitting.…”
Section: Electrochemical Reforming Of Alcoholsmentioning
confidence: 99%